Polarizing film with adhesive layer and image display device
By using an adhesive layer containing (meth)acrylic copolymer on the polarizing film, the problem of poor bonding of thin-film polarizing film at high temperature is solved, and the durability and display performance at high temperature is improved.
Patent Information
- Application Number
- CN202380051610.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-11
- Filing Date
- 2023-07-06
- Publication Date
- 2025-02-18
AI Technical Summary
Thin film polarizing films are prone to shrinking and warping in high temperature environments, resulting in poor bonding with image display elements, which in turn affects display performance.
A polarizing film with an adhesive layer having a moderate adhesive force is used, and the adhesive layer is formed of an adhesive composition containing a (meth)acrylic copolymer, and the copolymer contains 10 to 50 mass % of the average mass The monomer mixture of alkyl (meth)acrylate with a glass transition temperature of the polymer is above 0°C, and the gel fraction of the adhesive layer is greater than 80%.
In a high temperature environment, the shrinkage and warpage of the polarizing film is effectively suppressed, the foaming or peeling between it and the image display element is prevented, and the appropriate adhesion is maintained, and the display performance of the image display device is improved.
Smart Images

Figure BDA0005226011650000311 
Figure BDA0005226011650000361
Abstract
Description
Technical Field
[0001] One embodiment of the present invention relates to a polarizing film or an image display device with an adhesive layer. Background Art
[0002] Recently, image display devices are used in various applications such as televisions, mobile phones, and car navigation. Polarizing films, which are components of image display devices, are usually used by attaching them to image display elements via an adhesive layer. Therefore, polarizing films are sometimes sold as polarizing films with adhesive layers in which an adhesive layer is pre-set.
[0003] In recent years, thin image display devices with narrow frames have been actively developed, and at the same time, polarizing films are being thinned. As a thin-film type polarizing film, for example, Patent Document 1 discloses a polarizing film in which one of the protective layers provided on both sides of a polarizer is thinned. Prior art literature Patent Literature
[0004] Patent Document 1: Japanese Patent Application Publication No. 2007-58183 Summary of the invention
[0005] However, the film-type polarizing film may shrink the polarizer due to heat or humidity, and the polarizing film itself may shrink or warp. If the polarizing film shrinks or warps, it is easy to cause poor adhesion such as foaming or peeling between the adherend (such as an image display element) and the adhesive layer. This poor adhesion is one of the reasons for the decline in the display performance of the image display device.
[0006] Furthermore, in a high temperature environment such as in a car interior in summer, the polarizing plate shrinks significantly and is particularly susceptible to warping and the like. Therefore, a polarizing film with an adhesive layer used in an in-vehicle image display device is required to have durability under high temperatures.
[0007] The adhesive layer is also required to have an appropriate adhesive strength such that it does not peel or float from an adherend when used on the adherend and can be peeled from the adherend without leaving adhesive residue when peeled from the adherend (excellent re-adhesiveness).
[0008] One embodiment of the present invention provides a polarizing film with an adhesive layer that has moderate adhesive strength and is less likely to cause problems such as foaming and peeling due to warping of the polarizing film even in a high-temperature environment. Solutions to technical problems
[0009] The present inventors have conducted intensive research to solve the above technical problems. As a result, they have found that the above technical problems can be solved by the following means.
[0010] Embodiments of the present invention are as follows.
[0011] [1] A polarizing film with an adhesive layer, comprising: a polarizing film having a first protective layer provided on one side of a polarizer and a second protective layer provided on the other side of the polarizer, and an adhesive layer in contact with the second protective layer, The ratio of the thickness of the first protective layer to the thickness of the second protective layer, that is, the thickness of the second protective layer / the thickness of the first protective layer, is 0.1 to 0.7. The adhesive layer is a layer formed of an adhesive composition containing a (meth)acrylic polymer. The (meth)acrylic copolymer is a copolymer of a monomer mixture containing 10 to 50% by mass of an alkyl (meth)acrylate having a homopolymer glass transition temperature (Tg) of 0° C. or higher. The adhesive layer has a gel fraction greater than 80%.
[0012] [2] The polarizing film with an adhesive layer according to [1], wherein the (meth)acrylic copolymer has a weight average molecular weight (Mw) of 800,000 to 2,000,000.
[0013] [3] The polarizing film with an adhesive layer according to [1] or [2], wherein the (meth)acrylic copolymer has a molecular weight distribution (Mw / Mn) of 5 to 12.
[0014] [4] The polarizing film with an adhesive layer according to any one of [1] to [3], wherein the polarizing film has a thickness of 10 to 150 μm.
[0015] [5] The polarizing film with an adhesive layer as described in any one of [1] to [4], wherein the first protective layer and the second protective layer contain at least one resin selected from the group consisting of a (meth)acrylic resin, a cellulose resin, a cycloolefin polymer resin, and a polyvinyl alcohol resin.
[0016] [6] An image display device comprising the polarizing film with an adhesive layer as described in any one of [1] to [5] attached to an image display element. Effects of the Invention
[0017] According to one embodiment of the present invention, a polarizing film with an adhesive layer having moderate adhesive strength, which is less likely to cause problems such as bubbling or peeling due to shrinkage or warping of the polarizing film even in a high-temperature environment, and which is excellent in high-temperature durability can be provided.
[0018] In addition, when the polarizing film with an adhesive layer of one embodiment of the present invention is used in an image display device, even when the image display device is exposed to high temperature, it is possible to suppress the degradation of display performance caused by poor adhesion due to shrinkage or warping of the polarizing film. Therefore, the polarizing film with an adhesive layer of one embodiment of the present invention can be suitable for thin image display devices with narrow frames, and can be suitable for image display devices such as automotive devices that are exposed to high temperatures. DETAILED DESCRIPTION
[0019] 《Polarizing film with adhesive layer》 A polarizing film with an adhesive layer in one embodiment of the present invention (hereinafter also referred to as "the present polarizing film with an adhesive layer") comprises: a polarizing film having a first protective layer on one side of a polarizer and a second protective layer on the other side of the polarizer, and an adhesive layer in contact with the second protective layer, wherein the ratio of the thickness of the first protective layer to the second protective layer (thickness of the second protective layer / thickness of the first protective layer) is in the range of 0.1 to 0.7.
[0020] It is also characterized in that the adhesive layer is a layer formed by an adhesive composition containing a (meth)acrylic copolymer, wherein the (meth)acrylic copolymer is a copolymer of a monomer mixture of (meth)acrylic acid alkyl esters containing 10 to 50% by mass of a homopolymer having a glass transition temperature (Tg) of above 0°C, and the gel fraction of the adhesive layer is greater than 80%.
[0021] The reason why the present pressure-sensitive adhesive layer-attached polarizing film exhibits the above-mentioned effects is not necessarily clear, but is presumed to be, for example, as follows.
[0022] The present polarizing film with an adhesive layer is a polarizing film with an adhesive layer in which one side of the protective layer protecting the polarizer is thin, and an adhesive layer is provided on the side of the thin protective layer (second protective layer). Such a polarizing film with an adhesive layer is usually used by bringing the adhesive layer into contact with an adherend (the object to which the present polarizing film with an adhesive layer is adhered (e.g., an image display element)), so even if stress that causes the polarizing film to warp is generated at high temperatures, the direction of the stress changes from the polarizing film to the adherend direction (from the thick protective layer to the thin protective layer direction).
[0023] Moreover, the adhesive layer used in the polarizing film with an adhesive layer has a high degree of crosslinking and can form a layer with moderate viscoelasticity at high temperatures. Therefore, when the polarizing film shrinks, the stress concentrated in the edge part of the polarizing film, especially, can be dispersed, thereby suppressing the shrinkage of the polarizing film.
[0024] From the above, it can be inferred that in the polarizing film with an adhesive layer, while the shrinkage of the polarizing film itself is suppressed by the adhesive layer, there is an adhesive layer on the side of the thin second protective layer, and the stress that is easy to cause warping at the edge of the polarizing film is dispersed by the adhesive layer, thereby suppressing foaming or peeling at the bonding interface between the adherend and the adhesive layer, and can exert sufficient bonding performance even in a high temperature environment.
[0025] The polarizing film with adhesive layer includes a polarizing film and an adhesive layer stacked thereon. The polarizing film includes a polarizer, a first protective layer provided on one surface of the polarizer, and a second protective layer provided on the other surface of the polarizer. The adhesive layer stacked on the polarizing film is in contact with the second protective layer. That is, as one example of the layer structure of the polarizing film with adhesive layer, the structure of [first protective layer / polarizer / second protective layer / adhesive layer] can be cited.
[0026] The adhesive force of the present adhesive layer-attached polarizing film is preferably 1 to 10 N / 25 mm, more preferably 2 to 9 N / 25 mm, and even more preferably 3 to 8 N / 25 mm.
[0027] When the adhesive strength is within the above range, the polarizing film with an adhesive layer has excellent workability, re-adhesiveness, and adhesiveness.
[0028] The method for measuring the above-mentioned adhesive force will be described in detail in the examples described later.
[0029] <Polarizing film> As described above, the polarizing film is provided with a first protective layer on one side of the polarizer and a second protective layer on the other side of the polarizer. In this specification, the first protective layer and the second protective layer are collectively referred to as "protective layers".
[0030] In addition, the polarizing film may also have a phase difference film, an anti-glare layer, a viewing angle improvement layer, a hard coating layer, an anti-reflection layer, a light diffusion layer, an antistatic layer, an antifouling layer, a conductive layer, and other conventionally known films or layers in addition to the polarizer and the protective layer. However, the condition is that, as described above, the adhesive layer laminated on the polarizing film is in contact with the second protective layer in the polarizing film.
[0031] The thickness of the polarizing film is not particularly limited, but is preferably 10 μm or more, more preferably 15 μm or more, and preferably 150 μm or less, more preferably 100 μm or less.
[0032] A polarizing film having a thickness within the above range can be regarded as a thin-film type polarizing film, and is particularly susceptible to shrinkage and warping. Therefore, by using such a polarizing film and the adhesive layer, the above-mentioned effect of the present invention can be more effectively exerted.
[0033] In the present specification, films, sheets, and the like are not particularly distinguished, and film (sheet)-like molded bodies are collectively referred to as films.
[0034] [Protective layer] The ratio of the thickness of the first protective layer to the thickness of the second protective layer (the thickness of the second protective layer / the thickness of the first protective layer) is 0.1 to 0.7, preferably 0.1 to 0.6, and more preferably 0.2 to 0.5.
[0035] By making the ratio of the thickness of the above-mentioned protective layer within the above-mentioned range, the protective layer in contact with the adhesive layer becomes thinner. Therefore, even if it is assumed that stress that causes the polarizing film to warp is generated under high temperature, the direction of the stress will change from the polarizing film to the direction of the adherend, that is, to the direction of rolling the adhesive layer sideways inward. Therefore, even if the polarizing film is warped, the adhesive layer tends to be difficult to peel off from the adherend. On the other hand, if the ratio of the thickness of the above-mentioned protective layer exceeds the above-mentioned range and is closer to 1, that is, the thickness of the second protective layer is not much different from the thickness of the first protective layer, the adhesive layer will strongly act on the stress of the polarizing film shrinking in the horizontal direction, so the adhesive layer tends to be easily peeled off from the adherend. In addition, if the ratio of the thickness of the above-mentioned protective layer exceeds 1, the polarizing film is prone to warping, causing the polarizing film to flip up from the adherend, so the adhesive layer tends to be more easily peeled off from the adherend.
[0036] The thickness of the first protective layer and the second protective layer is not particularly limited as long as the ratio of the thickness of the two protective layers is within the above-mentioned range. The thickness of the first protective layer is preferably greater than 5 μm, more preferably greater than 10 μm, preferably less than 100 μm, more preferably less than 80 μm, and the thickness of the second protective layer is preferably greater than 3 μm, more preferably greater than 7 μm, preferably less than 60 μm, more preferably less than 50 μm.
[0037] As the components of the protective layer, for example, cellulose resins such as triacetyl cellulose (TAC), polyester resins, polyvinyl alcohol resins, polycarbonate resins, polyamide resins, polyimide resins, polyethersulfone resins, polysulfone resins, polystyrene resins, polynorbornene resins, polyolefin resins, cycloolefin polymer resins, (meth)acrylic resins, polyarylate resins, acetate resins, and mixtures of two or more selected from these resins are mentioned. Among them, cellulose resins, polyvinyl alcohol resins, polyester resins, polyethersulfone resins, polycarbonate resins, cycloolefin polymer resins, and (meth)acrylic resins are preferred, and cellulose resins, polyvinyl alcohol resins, cycloolefin polymer resins, and (meth)acrylic resins are more preferred.
[0038] The above-mentioned protective layers, i.e., the first protective layer and the second protective layer, are preferably layers containing at least one resin selected from (meth)acrylic resins, cellulose resins, cycloolefin polymer resins and polyvinyl alcohol resins, and more preferably layers with one resin selected from (meth)acrylic resins, cellulose resins, cycloolefin polymer resins and polyvinyl alcohol resins as the main component.
[0039] The above-mentioned “layer containing a resin as a main component” means a layer containing 50% by mass or more of a resin as a main component based on 100% by mass of the resin component constituting the protective layer.
[0040] The first protective layer and the second protective layer may be composed of the same component or different components.
[0041] In addition, as described above, when a conventionally known film or layer such as a retardation film is to be provided on the polarizing film, the functions of the film or layer may be imparted to the protective layer instead of providing the film or layer. For example, the protective layer may be a protective layer having the functions of a retardation film or the like.
[0042] For example, by stretching a film made of the above resin (uniaxial stretching or biaxial stretching, etc.) and forming a liquid crystal layer on the stretched film, a protective layer having the function of a retardation film imparting an arbitrary retardation value can be formed.
[0043] The protective layer may be subjected to a surface treatment as required, such as a hard coating treatment, an anti-reflection treatment, an anti-sticking treatment, and an anti-glare treatment, which may be appropriately selected.
[0044] [Polarizing plate] A polarizer is a film having the function of selectively transmitting linear polarized light in a certain direction from natural light. As the polarizer, for example, a stretched film obtained by stretching a film composed of a polyvinyl alcohol resin containing a polarizing component. As the polyvinyl alcohol resin, for example, polyvinyl alcohol, polyvinyl formal, polyvinyl acetal, and saponified products of ethylene-vinyl acetate copolymer can be mentioned. As the polarizing component, for example, iodine and / or a dichroic dye can be mentioned.
[0045] The thickness of the polarizer is not particularly limited, but is usually 0.1 μm or more, preferably 1 μm or more, and usually 100 μm or less, preferably 50 μm or less.
[0046] <Adhesive Layer> The adhesive layer used in the present polarizing film with an adhesive layer (hereinafter also referred to as "the present adhesive layer") is formed from an adhesive composition (hereinafter also referred to as "the present composition") containing a (meth)acrylic copolymer (hereinafter also referred to as "copolymer (a)"). The copolymer (a) is a copolymer of a monomer mixture containing 10 to 50% by mass of a homopolymer of an alkyl (meth)acrylate having a glass transition temperature (Tg) of 0°C or higher.
[0047] As described above, the adhesive layer can be a layer with a high degree of crosslinking and moderate viscoelasticity at high temperatures. By using the adhesive layer having such characteristics in combination with a polarizing film having the above characteristics, the polarizing film with the adhesive layer can suppress foaming or peeling at the bonding interface with the adherend, and can exert sufficient bonding performance even in a high temperature environment.
[0048] The adhesive layer is characterized in that the gel fraction is greater than 80%, preferably 81% or more, more preferably 82% or more, and preferably 95% or less, more preferably 90% or less.
[0049] By using an adhesive layer having a gel fraction within the above range, shrinkage of the polarizing film itself can be suppressed, and adhesion failures such as bubbles or cracks that may occur at the adhesion interface with an adherend can be suppressed.
[0050] The gel fraction can be measured by the method described in Examples below.
[0051] The thickness of the present adhesive layer can be appropriately set according to the purpose of the present adhesive layer, etc., and is not particularly limited, but is preferably 5 to 100 μm, and more preferably 10 to 50 μm.
[0052] In the present invention, the "(meth)acrylic (co)polymer" refers to a (co)polymer obtained by using a polymerizable monomer containing at least a (meth)acrylic acid ester.
[0053] In this specification, (meth)acrylic acid is used as a general term for acrylic acid and methacrylic acid, and may be either acrylic acid or methacrylic acid. In addition, (meth)acrylate is used as a general term for acrylate and methacrylate, and may be either acrylate or methacrylate. In addition, (meth)acryloyl is used as a general term for acryloyl and methacryloyl, and may be either acryloyl or methacryloyl.
[0054] [Copolymer (a)] The copolymer (a) is a copolymer of a monomer mixture containing 10 to 50% by mass of an alkyl (meth)acrylate having a homopolymer glass transition temperature (Tg) of 0° C. or higher (hereinafter also referred to as “alkyl (meth)acrylate (A)”).
[0055] By using such a copolymer (a), the adhesive force and re-tackiness (re-stickability) of the resulting adhesive layer tend to be easily adjusted, and an adhesive layer excellent in high-temperature durability tends to be formed.
[0056] The copolymer (a) contained in the present composition may be one kind or two or more kinds.
[0057] [Alkyl (meth)acrylate (A)] The monomer mixture as a raw material of the copolymer (a) contains 10 to 50% by mass of the alkyl (meth)acrylate (A). That is, the copolymer (a) contains 10 to 50% by mass of a structural unit derived from the alkyl (meth)acrylate (A).
[0058] When the copolymer (a) contains a predetermined amount of structural units derived from the (meth)acrylate alkyl ester (A), the adhesive layer tends to have appropriate viscoelasticity at high temperatures and the stress concentrated on the edge of the polarizing film tends to be dispersed while suppressing shrinkage of the polarizing film.
[0059] As said alkyl (meth)acrylate (A), the alkyl (meth)acrylate whose alkyl group has 1 to 12 carbon atoms may be mentioned, for example.
[0060] The carbon number of the alkyl group is preferably 1 to 8, more preferably 1 to 4. The alkyl group may be a linear alkyl group or a branched alkyl group, but is preferably a linear alkyl group.
[0061] Examples of the (meth)acrylic acid alkyl ester (A) include methyl acrylate (Tg: 8°C), methyl methacrylate (Tg: 105°C), ethyl methacrylate (Tg: 65°C), n-propyl acrylate (Tg: 3°C), n-propyl methacrylate (Tg: 35°C), isopropyl methacrylate (Tg: 81°C), n-butyl methacrylate (Tg: 20°C), isobutyl methacrylate (Tg: 48°C), tert-butyl acrylate (Tg: 43°C), tert-butyl methacrylate (Tg: 118°C), and pentyl acrylate (Tg: 22°C).
[0062] In addition, Tg in the above paragraph is Tg of the homopolymer of each (meth)acrylate.
[0063] As the alkyl (meth)acrylate (A), from the viewpoint of further exerting the above-mentioned effects, methyl acrylate and methyl methacrylate are preferred, and methyl acrylate is more preferred.
[0064] The (meth)acrylic acid alkyl ester (A) may be used alone or in combination of two or more.
[0065] The glass transition temperature (Tg) of the homopolymer of the alkyl (meth)acrylate (A) is 0°C or higher, preferably 0 to 120°C, and more preferably 0 to 100°C.
[0066] When Tg is within the above range, the adhesive layer can have appropriate viscoelasticity at high temperatures, and the durability of the obtained adhesive layer can be improved.
[0067] In addition, the glass transition temperature of a homopolymer prepared from a representative monomer is described in, for example, Polymer Handbook Fourth Edition (Wiley-Ircience, 2003).
[0068] From the viewpoint of more effectively exerting the above-mentioned effects, the content of the alkyl (meth)acrylate (A) in the monomer mixture is 10 to 50% by mass, preferably 10 to 40% by mass, and more preferably 10 to 30% by mass.
[0069] [Monomers other than (meth)acrylic acid alkyl ester (A)] The raw material of the copolymer (a), i.e., the monomer mixture, contains 50 to 90% by mass of monomers other than the (meth) alkyl ester (A). That is, the copolymer (a) contains 50 to 90% by mass of structural units derived from monomers other than the (meth) alkyl ester (A). From the perspective of being able to better exert the above-mentioned effects, the content of the monomers other than the (meth) alkyl ester (A) in the monomer mixture is 50 to 90% by mass, preferably 60 to 90% by mass, and more preferably 70 to 90% by mass.
[0070] Examples of monomers other than the above-mentioned alkyl (meth)acrylate (A) include alkyl (meth)acrylates other than the above-mentioned alkyl (meth)acrylate (A) (hereinafter also referred to as "alkyl (meth)acrylate (B)"), alkoxyalkyl (meth)acrylates, alicyclic hydrocarbon group-containing (meth)acrylates, aromatic hydrocarbon group-containing (meth)acrylates, styrene-based monomers, vinyl ester compounds, crosslinkable functional group-containing monomers, and the like.
[0071] The monomers other than the (meth)acrylic acid alkyl ester (A) may be used alone or in combination of two or more.
[0072] (Alkyl (meth)acrylate (B)) The alkyl (meth)acrylate (B) is an alkyl (meth)acrylate having a homopolymer glass transition temperature (Tg) of less than 0°C, and the Tg is preferably -80 to -10°C, more preferably -60 to -10°C.
[0073] It is preferable to use the (meth)acrylate (B) having a Tg within the above range because the resulting adhesive layer tends to have moderate stress relaxation properties.
[0074] The carbon number of the alkyl group in the (meth)acrylate (B) is preferably 2 to 20, more preferably 2 to 12, and even more preferably 4 to 10. The alkyl group may be a linear alkyl group or a branched alkyl group.
[0075] Examples of the alkyl (meth)acrylate (B) include ethyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, amyl methacrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, n-nonyl (meth)acrylate, isononyl (meth)acrylate, n-decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, lauryl (meth)acrylate, oleyl (meth)acrylate, n-stearyl (meth)acrylate, and isostearyl (meth)acrylate.
[0076] The (meth)acrylic acid alkyl ester (B) may be used alone or in combination of two or more.
[0077] When the copolymer (a) contains a structural unit derived from the (meth)acrylate (B), the cohesive force and stress relaxation properties of the resulting adhesive layer tend to be easily adjustable.
[0078] When the alkyl (meth)acrylate (B) is used, the content of the alkyl (meth)acrylate (B) in the monomer mixture is preferably 50 to 90% by mass, more preferably 50 to 89% by mass, from the viewpoint of more exerting the above-mentioned effects.
[0079] (Alkoxyalkyl (meth)acrylate) Examples of the alkoxyalkyl (meth)acrylate include methoxymethyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 3-methoxypropyl (meth)acrylate, 3-ethoxypropyl (meth)acrylate, 4-methoxybutyl (meth)acrylate, and 4-ethoxybutyl (meth)acrylate.
[0080] The alkoxyalkyl (meth)acrylates may be used alone or in combination of two or more.
[0081] When the copolymer (a) contains a structural unit derived from an alkoxyalkyl (meth)acrylate, the time until the physical properties (e.g., gel fraction) of the resulting adhesive layer remain unchanged tends to be shortened (also referred to as "excellent aging properties"), so an adhesive layer with excellent quality stability can be formed with good productivity.
[0082] When an alkoxyalkyl (meth)acrylate is used, the content of the alkoxyalkyl (meth)acrylate in the monomer mixture is preferably 50 to 90% by mass, more preferably 50 to 89% by mass, from the viewpoint of more exerting the above-mentioned effects.
[0083] (Alicyclic hydrocarbon group-containing (meth)acrylate) Examples of the alicyclic hydrocarbon group-containing (meth)acrylate include cyclohexyl (meth)acrylate, 4-tert-butylcyclohexyl (meth)acrylate, isobornyl (meth)acrylate and adamantyl (meth)acrylate.
[0084] The alicyclic hydrocarbon group-containing (meth)acrylate may be used alone or in combination of two or more.
[0085] When the copolymer (a) contains a structural unit derived from an alicyclic hydrocarbon group-containing (meth)acrylate, the cohesive force and stress relaxation properties of the resulting adhesive layer tend to be easily adjustable.
[0086] When an alicyclic hydrocarbon group-containing (meth)acrylate is used, the content of the alicyclic hydrocarbon group-containing (meth)acrylate in the monomer mixture is preferably less than 30% by mass, more preferably 20% by mass or less, from the viewpoint of better exerting the above-mentioned effects.
[0087] (Aromatic hydrocarbon group-containing (meth)acrylate) Examples of the aromatic hydrocarbon group-containing (meth)acrylate include benzyl (meth)acrylate, phenyl (meth)acrylate, and phenoxyethyl (meth)acrylate.
[0088] The aromatic hydrocarbon group-containing (meth)acrylate may be used alone or in combination of two or more.
[0089] By making the copolymer (a) contain a structural unit derived from an aromatic hydrocarbon group-containing (meth)acrylate, it tends to be easy to form an adhesive layer that can suppress birefringence and has excellent optical properties. Therefore, when an aromatic hydrocarbon group-containing (meth)acrylate is used in the monomer mixture, it is preferably used in the following content range.
[0090] When an aromatic hydrocarbon group-containing (meth)acrylate is used, the content of the aromatic hydrocarbon group-containing (meth)acrylate in the monomer mixture is preferably less than 30% by mass, more preferably 20% by mass or less, from the viewpoint of better exerting the above-mentioned effects.
[0091] (Styrene monomers and vinyl ester compounds) Examples of the styrene-based monomer include styrene, α-methylstyrene, p-methylstyrene, p-chlorostyrene, p-chloromethylstyrene, p-methoxystyrene, p-tert-butoxystyrene, divinylbenzene and indene.
[0092] The styrene-based monomers may be used alone or in combination of two or more.
[0093] Examples of the vinyl ester compound include vinyl acetate, vinyl propionate, vinyl butyrate, vinyl caproate, vinyl benzoate and vinyl cinnamate.
[0094] The vinyl ester compound may be used alone or in combination of two or more.
[0095] When the styrene-based monomer and the vinyl ester compound are used, the content of these monomers in the monomer mixture is not particularly limited, but is preferably 10% by mass or less, and more preferably 5% by mass or less.
[0096] (Monomer containing cross-linking functional group) The "crosslinkable functional group" in the crosslinkable functional group-containing monomer refers to a functional group that can react with a crosslinking agent to form a crosslink.
[0097] The crosslinkable functional group-containing monomer is preferably a (meth)acrylic compound having a crosslinkable functional group.
[0098] Examples of the crosslinkable functional group include acidic groups such as a carboxyl group and a carbonyl group, a hydroxyl group, an amino group, an amide group, an epoxy group, and a cyano group. Among them, a hydroxyl group, an amino group, and a carboxyl group are preferred.
[0099] When the monomer containing a cross-linkable functional group is used, the content of the monomer containing a cross-linkable functional group in the monomer mixture is preferably 0.01 to 10% by mass, more preferably 0.01 to 7% by mass, and further preferably 0.01 to 4% by mass, from the perspective of appropriately forming a cross-linked structure of the copolymer (a) and obtaining an adhesive layer having appropriate softness.
[0100] Furthermore, the copolymer of the monomer mixture in which the content of the crosslinkable functional group-containing monomer is within the above range can be said to be a copolymer in which the content of the structural unit derived from the crosslinkable functional group-containing monomer is within the above range.
[0101] The crosslinkable functional group-containing monomer may be used alone or in combination of two or more.
[0102] Examples of the hydroxyl-containing monomer include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, and (4-hydroxymethylcyclohexyl)methyl (meth)acrylate.
[0103] The hydroxyl group-containing monomer may be used alone or in combination of two or more.
[0104] When a hydroxyl-containing monomer is used, the content of the hydroxyl-containing monomer in the monomer mixture is preferably 0.01 to 7% by mass, more preferably 0.01 to 4% by mass, from the perspective that the resulting adhesive layer is likely to have a moderate crosslinking density, and that an adhesive layer having excellent stress relaxation properties and not easily peeled from an adherend can be easily formed.
[0105] Examples of the amino group-containing monomer include dialkylaminoalkyl (meth)acrylates such as dimethylaminoethyl (meth)acrylate and diethylaminoethyl (meth)acrylate.
[0106] The amino group-containing monomer may be used alone or in combination of two or more.
[0107] In addition, since an amide group or an imide group is generally not included in an amino group, in the present invention, a monomer having an amide group or an imide group and having no amino group other than the amide group or the imide group is not an amino group-containing monomer.
[0108] When an amino-containing monomer is used, the content of the amino-containing monomer in the monomer mixture is preferably 0.01 to 7% by mass, more preferably 0.01 to 4% by mass, from the perspective of making the resulting adhesive layer have a moderate crosslinking density, tending to easily form an adhesive layer that has excellent stress relaxation properties and is not easily peeled from the adherend, etc.
[0109] Examples of the acidic group-containing monomer include carboxyl group-containing monomers such as acrylic acid, methacrylic acid, β-carboxyethyl (meth)acrylate, 5-carboxypentyl (meth)acrylate, mono(meth)acryloyloxyethyl succinate, ω-carboxypolycaprolactone mono(meth)acrylate, crotonic acid, maleic acid, fumaric acid, itaconic acid, and citraconic acid.
[0110] The acidic group-containing monomer may be used alone or in combination of two or more.
[0111] When using a monomer containing an acidic group, the content of the monomer containing an acidic group in the monomer mixture is preferably 0.01 to 7% by mass, more preferably 0.01 to 4% by mass, from the viewpoint that the obtained adhesive layer can easily form a layer having a moderate crosslinking density, and tends to be able to easily form an adhesive layer having excellent stress relaxation properties and not easily peeled from the adherend.
[0112] However, in one embodiment of the present invention, when corrosion caused by acid components of an adherend to which the adhesive layer is attached becomes a problem, for example, when the adhesive layer formed by the present composition is in direct contact with an adherend that is easily corroded by acid components, such as a metal oxide layer such as ITO (indium tin composite oxide) or a conductive layer of a metal mesh containing metal (thin) wires formed into a lattice pattern, the content of the monomer containing an acidic group is preferably 0.4% or less, and more preferably 0.3% or less, from the perspective of being able to easily suppress corrosion, etc. In one embodiment of this case, it is preferred to use a monomer containing a crosslinkable functional group other than the monomer containing an acidic group instead of using a monomer containing an acidic group.
[0113] Examples of other monomers containing crosslinkable functional groups other than the above-mentioned monomers include: (meth)acrylamide; N-alkyl (meth)acrylamide such as N-methyl (meth)acrylamide, N-ethyl (meth)acrylamide, N-propyl (meth)acrylamide, and N-hexyl (meth)acrylamide; N,N-dialkyl (meth)acrylamide such as N,N-dimethyl (meth)acrylamide and N,N-diethyl (meth)acrylamide; amide group-containing monomers such as cyclic amide group-containing monomers such as N-vinylpyrrolidone, N-vinylcaprolactam, and (meth)acryloylmorpholine; nitrogen-containing heterocyclic monomers such as N-cyclohexylmaleimide, N-phenylmaleimide, N-lauroylmaleimide, and N-benzylmaleimide; and cyano group-containing monomers such as acrylonitrile and methacrylonitrile.
[0114] The above-mentioned other crosslinkable functional group-containing monomers may be used alone or in combination of two or more.
[0115] When the above-mentioned other crosslinkable functional group-containing monomer is used, the content of the other crosslinkable functional group-containing monomer in the above-mentioned monomer mixture is preferably 0.01 to 7% by mass, and more preferably 0.01 to 4% by mass.
[0116] [Method for synthesizing copolymer (a)] The copolymer (a) can be synthesized by polymerizing the above-mentioned monomer mixture, and can be, for example, a random polymer, a block polymer or a graft polymer, and can be synthesized by various polymerization methods. The polymerization method is not particularly limited, and for example, solution polymerization, bulk polymerization, emulsion polymerization, and suspension polymerization can be exemplified. Among them, when the copolymer obtained by polymerization is used to manufacture the present composition, it is preferably polymerized by solution polymerization from the perspective that the processing steps are relatively simple and can be carried out in a short time.
[0117] As a specific example of solution polymerization, a method can be cited in which a monomer mixture, a polymerization initiator, and other components such as a chain transfer agent and a polymerization solvent used as needed are added to a reaction vessel, the reaction start temperature is set to usually 40 to 100° C., preferably 50 to 80° C., the reaction system is maintained at a temperature of usually 50 to 90° C., preferably 60 to 90° C., and the reaction system is reacted for 2 to 20 hours. The reaction is carried out, for example, under an inert gas atmosphere such as nitrogen. In addition, in the polymerization reaction, at least one selected from a monomer mixture, a polymerization initiator, a chain transfer agent, and a polymerization solvent may be added.
[0118] As a polymerization initiator, an azo type initiator and a peroxide type polymerization initiator are mentioned, for example.
[0119] Examples of the azo initiator include 2,2'-azobisisobutyronitrile, 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2'-azobis(2-cyclopropylpropionitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2-methylbutyronitrile), 1,1'-azobis(cyclohexane-1-carbonitrile), 2-(carbamoylazo)isobutyronitrile, 2-phenylazo-4-methoxy-2,4-dimethylvaleronitrile, ... Azo compounds such as 2,2'-azobis(aminobispropane) dihydrochloride, 2,2'-azobis(N,N'-dimethylisobutylamidine), 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)-propionamide], 2,2'-azobis(isobutylamine) diacetate, 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis(2-cyanopropanol), dimethyl-2,2'-azobis(2-methylpropionate), and 2,2'-azobis(2-methyl-N-(2-hydroxyethyl)propionamide).
[0120] Examples of the peroxide polymerization initiator include tert-butyl hydroperoxide, cumene hydroperoxide, diisopropylbenzene hydroperoxide, benzoyl peroxide, lauroyl peroxide, hexanoyl peroxide, diisopropyl peroxydicarbonate, di-2-ethylhexyl peroxydicarbonate, tert-butyl peroxypivalate, 2,2-bis(4,4-di-tert-butylperoxycyclohexyl)propane, 2,2-bis(4,4-di-tert-amylperoxycyclohexyl)propane, 2,2-bis(4,4-di-tert-octylperoxycyclohexyl)propane, 2,2-bis(4,4-di-α-isopropylphenylperoxycyclohexyl)propane, 2,2-bis(4,4-di-tert-butylperoxycyclohexyl)butane, and 2,2-bis(4,4-di-tert-octylperoxycyclohexyl)butane.
[0121] The above-mentioned polymerization initiator may be used alone or in combination of two or more. In addition, the polymerization initiator may be added multiple times during the polymerization.
[0122] The amount of the polymerization initiator used is preferably 0.001 to 5 parts by mass, more preferably 0.005 to 3 parts by mass, based on 100 parts by mass of the monomer mixture.
[0123] Examples of the polymerization solvent used in the solution polymerization include aromatic hydrocarbons such as benzene, toluene and xylene; aliphatic hydrocarbons such as n-pentane, n-hexane, n-heptane and n-octane; alicyclic hydrocarbons such as cyclopentane, cyclohexane, cycloheptane and cyclooctane; ethers such as diethyl ether, diisopropyl ether, 1,2-dimethoxyethane, dibutyl ether, tetrahydrofuran, dioxane, anisole, phenethyl ether and diphenyl ether; halogenated hydrocarbons such as chloroform, carbon tetrachloride, 1,2-dichloroethane and chlorobenzene; esters such as ethyl acetate, propyl acetate, butyl acetate and methyl propionate; ketones such as acetone, methyl ethyl ketone, diethyl ketone, methyl isobutyl ketone and cyclohexanone; amides such as N,N-dimethylformamide, N,N-dimethylacetamide and N-methylpyrrolidone; nitriles such as acetonitrile and benzonitrile; and sulfoxides such as dimethyl sulfoxide and cyclopentane.
[0124] The above-mentioned polymerization solvents may be used alone or in combination of two or more.
[0125] [Physical Properties of Copolymer (a)] The weight average molecular weight (Mw) of the copolymer (a) measured by gel permeation chromatography (GPC) is preferably 800,000 to 2,000,000, more preferably 1,200,000 to 2,000,000, and even more preferably 1,500,000 to 2,000,000.
[0126] When Mw is within the above range, an adhesive layer having excellent durability and cohesive force tends to be easily formed.
[0127] The molecular weight distribution (Mw / Mn) of the copolymer (a) is preferably 4-12, more preferably 5-12, further preferably 5-10, and particularly preferably 5-8.
[0128] When Mw / Mn is within the above range, the resulting adhesive layer tends to be able to easily suppress foaming at the bonding interface with the adherend. This is presumably because, when the polarizing film shrinks, the uncrosslinked polymer can flow in the adhesive layer according to the stress, thereby easily suppressing foaming at the bonding interface with the adherend.
[0129] The above-mentioned Mw and Mw / Mn can be specifically measured by the method described in the following Examples.
[0130] From the perspective of being able to easily form an adhesive layer having moderate adhesive strength, being less likely to suffer from crack-like poor adhesion or peeling from the adherend even at high temperatures, and having excellent high-temperature durability, the glass transition temperature (Tg) calculated according to the Fox equation of the copolymer (a) is preferably -65 to 0°C, more preferably -55 to 0°C, and even more preferably -45 to 0°C.
[0131] Fox formula: 1 / Tg = (W1 / Tg1) + (W2 / Tg2) + ... + (W m / Tg m ) W1+W2+……+W m =1 Wherein, Tg is the glass transition temperature of copolymer (a) (unit K), Tg1, Tg2, ..., Tg m is the glass transition temperature (unit K) of the homopolymer formed by each monomer, W1, W2, ..., W m is the mass fraction of the structural unit derived from each monomer in the copolymer (a). As the mass fraction of the structural unit derived from each monomer, the addition ratio of each monomer relative to all monomers during the synthesis of the copolymer (a) can be used.
[0132] In addition, the glass transition temperature of a homopolymer prepared from a representative monomer is described in, for example, Polymer Handbook Fourth Edition (Wiley-Ircience, 2003).
[0133] [Content of copolymer (a)] The content of the copolymer (a) is preferably 50 to 99.98% by mass, more preferably 70 to 99.95% by mass, based on 100% by mass of the nonvolatile components of the present composition.
[0134] When the content of the copolymer (a) is within the above range, an adhesive layer having moderate adhesive strength, a good balance between cohesive force and stress relaxation properties even under high temperature or high humidity, and being less likely to foam or peel from an adherend can be easily formed.
[0135] [Other ingredients] Without prejudice to the effects of the present invention, the present composition may also contain other ingredients in addition to the above-mentioned copolymer (a), such as a crosslinking agent, a silane coupling agent, a polymer other than the copolymer (a), an antistatic agent, a tackifying resin, an antioxidant, a light stabilizer, a metal corrosion inhibitor, a plasticizer, a crosslinking accelerator, a reprocessing agent, and an organic solvent.
[0136] These other components may be used alone or in combination of two or more.
[0137] [Crosslinking agent] The crosslinking agent is not particularly limited as long as it can crosslink the copolymer (a). Examples of the crosslinking agent include isocyanate compounds, epoxy compounds, and metal chelate compounds.
[0138] The cross-linking agent may be used alone or in combination of two or more.
[0139] When the present composition contains a crosslinking agent, the copolymer (a) is crosslinked to form a crosslinked body (network polymer), and thus an adhesive layer having excellent adhesive force and heat resistance tends to be easily formed.
[0140] (Isocyanate compound) As the isocyanate compound, for example, an isocyanate compound having 2 or more isocyanate groups in one molecule is generally used, and the number of isocyanate groups in one molecule is preferably 2 to 8, and more preferably 3 to 6. The isocyanate group number within the above range is preferred from the perspective of maintaining the efficiency of the crosslinking reaction between the copolymer (a) and the isocyanate compound and the flexibility of the resulting adhesive layer.
[0141] Examples of the diisocyanate compound having two isocyanate groups in one molecule include aliphatic diisocyanate, alicyclic diisocyanate and aromatic diisocyanate.
[0142] Examples of the aliphatic diisocyanate include aliphatic diisocyanates having 4 to 30 carbon atoms, such as ethylene diisocyanate, tetramethylene diisocyanate, pentamethylene diisocyanate, hexamethylene diisocyanate, 2-methyl-1,5-pentane diisocyanate, 3-methyl-1,5-pentane diisocyanate, and 2,2,4-trimethyl-1,6-hexamethylene diisocyanate.
[0143] Examples of the alicyclic diisocyanate include alicyclic diisocyanates having 7 to 30 carbon atoms, such as isophorone diisocyanate, cyclopentyl diisocyanate, cyclohexyl diisocyanate, hydrogenated xylene diisocyanate, hydrogenated toluene diisocyanate, hydrogenated diphenylmethane diisocyanate and hydrogenated tetramethylxylene diisocyanate.
[0144] Examples of the aromatic diisocyanate include aromatic diisocyanates having 8 to 30 carbon atoms, such as phenylene diisocyanate, toluene diisocyanate, xylene diisocyanate, naphthalene diisocyanate, diphenyl ether diisocyanate, diphenylmethane diisocyanate and diphenylpropane diisocyanate.
[0145] Examples of the isocyanate compound having three or more isocyanate groups in one molecule include aromatic polyisocyanates, aliphatic polyisocyanates, and alicyclic polyisocyanates. Specifically, examples include 2,4,6-triisocyanatotoluene, 1,3,5-triisocyanatobenzene, and 4,4',4"-triphenylmethane triisocyanate.
[0146] In addition, examples of isocyanate compounds include: polymers (e.g., dimers or trimers, biuret bodies, isocyanurate bodies) of the above-mentioned isocyanate crosslinking agents having 2 or 3 or more isocyanate groups, derivatives (e.g., addition reaction products of polyols and 2 or more molecules of diisocyanate crosslinking agents), and polymers. Examples of the polyols in the above-mentioned derivatives include trivalent or higher alcohols such as trimethylolpropane, glycerol, and pentaerythritol as low molecular weight polyols; examples of high molecular weight polyols include polyether polyols, polyester polyols, acrylic polyols, polybutadiene polyols, and polyisoprene polyols.
[0147] Examples of such isocyanate compounds include trimers of diphenylmethane diisocyanate, polymethylene polyphenyl polyisocyanates, biuret forms or isocyanurate forms of hexamethylene diisocyanate or toluene diisocyanate, reaction products of trimethylolpropane with toluene diisocyanate or xylene diisocyanate (e.g., 3-molecule adducts of toluene diisocyanate or xylene diisocyanate), reaction products of trimethylolpropane with hexamethylene diisocyanate (e.g., 3-molecule adducts of hexamethylene diisocyanate), polyether polyisocyanates, and polyester polyisocyanates.
[0148] Among the isocyanate compounds, from the viewpoint of yellowing resistance, xylene diisocyanate-based and hexamethylene diisocyanate-based crosslinking agents are preferred, and from the viewpoint of stress relaxation, toluene diisocyanate-based crosslinking agents are preferred. Examples of xylene diisocyanate-based crosslinking agents include xylene diisocyanate and multimers, derivatives, and polymers thereof, examples of hexamethylene diisocyanate-based crosslinking agents include hexamethylene diisocyanate and multimers, derivatives, and polymers thereof, and examples of toluene diisocyanate-based crosslinking agents include toluene diisocyanate and multimers, derivatives, and polymers thereof.
[0149] (Epoxides) Examples of the epoxy compound include compounds having two or more epoxy groups in one molecule, such as ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, glycerol diglycidyl ether, glycerol triglycidyl ether, 1,6-hexanediol diglycidyl ether, trimethylolpropane triglycidyl ether, diglycidyl aniline, diamine glycidyl amine, N,N,N',N'-tetraglycidyl-m-xylene diamine, 1,3-bis(N,N'-diamine glycidylaminomethyl)cyclohexane, triglycidyl isocyanurate, m-N,N-diglycidylaminophenyl glycidyl ether, N,N-diglycidyl aniline, and pentaerythritol polyglycidyl ether.
[0150] (Metal Chelate Compounds) Examples of the metal chelate compounds include compounds in which alkoxides, acetylacetone, ethyl acetylacetonate, etc. are coordinated to polyvalent metals such as aluminum, iron, copper, zinc, tin, titanium, nickel, antimony, magnesium, vanadium, chromium, and zirconium. Specifically, examples include aluminum isopropoxide, aluminum sec-butyrate, aluminum ethyl acetylacetonate diisopropoxide, aluminum triethyl acetylacetonate, and aluminum triacetylacetonate.
[0151] When the present composition contains a crosslinking agent, the content of the crosslinking agent is preferably 0.01 to 30 parts by mass, more preferably 0.05 to 25 parts by mass, based on 100 parts by mass of the copolymer (a).
[0152] [Silane coupling agent] The present composition contains a silane coupling agent, thereby tending to be able to easily form an adhesive layer having high adhesive strength to an adherend.
[0153] The above-mentioned silane coupling agents may be used alone or in combination of two or more.
[0154] Examples of the silane coupling agent include: silane coupling agents containing polymerizable unsaturated groups such as vinyltrimethoxysilane, vinyltriethoxysilane, and methacryloxypropyltrimethoxysilane; silane coupling agents containing epoxy groups such as 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; silane coupling agents containing amino groups such as 3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, and N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane; and silane coupling agents containing halogens such as 3-chloropropyltrimethoxysilane. Among them, epoxy group-containing silane coupling agents are preferred because they tend to easily form an adhesive layer excellent in stress relaxation properties.
[0155] When the present composition contains a silane coupling agent, the content of the silane coupling agent is usually 1 part by mass or less, preferably 0.01 to 1 part by mass, and more preferably 0.05 to 0.5 parts by mass, relative to 100 parts by mass of the copolymer (a). When two or more silane coupling agents are used, the total content of the silane coupling agents used can be within the above range.
[0156] When the content of the silane coupling agent is within the above range, it tends to be easy to form an adhesive layer that can suppress the adhesive layer from being peeled off from the adherend even in a high-humidity and hot environment and that does not easily cause the silane coupling agent to bleed out even in a high-temperature environment.
[0157] [Polymers other than copolymer (a)] The polymer other than the copolymer (a) (hereinafter also referred to as "polymer (b)") is not particularly limited, but is preferably a (meth)acrylic (co)polymer. The polymer (b) may be a homopolymer or a copolymer.
[0158] The polymer (b) may be used alone or in combination of two or more.
[0159] As the (meth)acrylic (co)polymer of the polymer (b), there may be mentioned a polymer in which the content of the (meth)acrylic acid alkyl ester (A) in its raw material, i.e., monomer component, is less than 10% by mass or exceeds 50% by mass, and the upper limit of the content is usually below 90% by mass.
[0160] The Mw of the (meth)acrylic (co)polymer as the polymer (b) is not particularly limited, but is preferably 5,000 to 2,000,000, more preferably 10,000 to 2,000,000, and even more preferably 10,000 to 1,500,000.
[0161] As the raw material, i.e., monomer, of the (meth)acrylic (co)polymer of the polymer (b), the same monomer as described in the above-mentioned copolymer (a) can be cited, and as the synthesis method of the (meth)acrylic (co)polymer of the polymer (b), the same method as the synthesis method of the above-mentioned copolymer (a) can be cited.
[0162] When the present composition contains the polymer (b), the content of the polymer (b) is preferably 2 to 100 parts by mass, more preferably 5 to 80 parts by mass, based on 100 parts by mass of the copolymer (a).
[0163] When the content of the copolymer (b) is within the above range, stress generated by shrinkage of the polarizing film tends to be easily alleviated, and problems such as peeling tend to be less likely to occur.
[0164] [Antistatic Agent] As the antistatic agent, for example, there can be mentioned surfactants, ionic compounds, and conductive polymers.
[0165] The above antistatic agents may be used alone or in combination of two or more.
[0166] Examples of the surfactant include: cationic surfactants having cationic groups such as quaternary ammonium salts, amide quaternary ammonium salts, pyridinium salts, and primary to tertiary amino groups; anionic surfactants having anionic groups such as sulfonate groups, sulfate groups, and phosphate groups; amphoteric surfactants such as alkyl betaines, alkyl imidazoline betaines, alkylamine oxides, and amino acid sulfates; and nonionic surfactants such as glycerol fatty acid esters, sorbitan fatty acid esters, polyoxyethylene alkylamines, polyoxyethylene alkylamine fatty acid esters, N-hydroxyethyl-N-2-hydroxyalkylamines, and alkyl diethanolamides.
[0167] In addition, as the surfactant, a reactive emulsifier having a polymerizable group may be mentioned, and a polymer surfactant obtained by increasing the molecular weight of a monomer component containing the above-mentioned surfactant or reactive emulsifier may also be used.
[0168] The ionic compound is a compound composed of a cation part and an anion part, and may be a solid compound or a liquid compound at room temperature (23° C.) and 50% RH.
[0169] The cation part constituting the ionic compound may be either an inorganic cation or an organic cation, or both. As the inorganic cation, alkali metal ions and alkaline earth metal ions are preferred, and Li ions having excellent antistatic properties are more preferred. + 、Na + and K + Examples of the organic cation include pyridinium cations, piperidinium cations, pyrrolidinium cations, pyrrolinium cations, pyrrole cations, imidazolium cations, tetrahydropyridinium cations, dihydropyridinium cations, pyrazolium cations, pyrazolinium cations, tetraalkylammonium cations, trialkylalkoxyammonium cations, trialkylsulfonium cations, tetraalkylphosphonium cations, and derivatives thereof.
[0170] The anion part constituting the ionic compound is not particularly limited as long as it can form an ionic compound by ion bonding with the cation part. - , Cl - Br - ,I - 、AlCl4 - 、Al2Cl7 - 、BF4 - PF6 - 、SCN - 、ClO4 -、NO3 - 、CH3COO - CF3COO - 、CH3SO3 - CF3SO3 - 、(CF3SO2)2N - 、(FSO2)2N - 、(CF3SO2)3C - 、AsF6 - 、SbF6 - 、NbF6 - 、TaF6 - 、F(HF) n - (n is 1 to 3), (CN)2N - 、C4F9SO3 - 、(C2F5SO2)2N - 、C3F7COO - and (CF3SO2)(CF3CO)N - .
[0171] Examples of the ionic compound include lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium tris(trifluoromethylsulfonyl)methane, potassium bis(trifluoromethylsulfonyl)imide, potassium bis(fluorosulfonyl)imide, 1-ethylpyridinium hexafluorophosphate, 1-butylpyridinium hexafluorophosphate, 1-hexyl-4-methylpyridinium hexafluorophosphate, 1-octyl-4-methylpyridinium hexafluorophosphate, 1-octyl-4-methylpyridinium bis(fluorosulfonyl)imide, 1-octyl-4-methylpyridinium bis(trifluoromethylsulfonyl)imide, N,N-diethyl-N-methyl-N-(2-methoxyethyl)ammonium tetrafluoroborate, N,N-diethyl-N-methyl-N-(2-methoxyethyl)ammonium bis(trifluoromethylsulfonyl)imide, 1-octylpyridinium fluorosulfonylimide, and 1-octyl-3-methylpyridinium trifluorosulfonylimide.
[0172] The conductive polymer may, for example, be polythiophene, polyaniline, polypyrrole or a derivative thereof.
[0173] When the present composition contains an antistatic agent, the content of the antistatic agent is preferably 5 parts by mass or less, more preferably 0.1 to 5 parts by mass, and even more preferably 1 to 5 parts by mass, based on 100 parts by mass of the copolymer (a).
[0174] [Organic solvents] The composition of the present invention may contain an organic solvent within a range not impairing the effects of the present invention.
[0175] The above-mentioned organic solvents may be used alone or in combination of two or more.
[0176] As the organic solvent, for example, there may be mentioned the same solvents as the polymerization solvents described in the section of the synthesis method of the copolymer (a).
[0177] As the present composition containing such an organic solvent, for example, when preparing the present composition, an organic solvent may be used, or a polymer solution containing the copolymer (a) and a polymerization solvent may be used.
[0178] The content of the organic solvent in the present composition is, for example, 0 to 90 mass %, or preferably 10 to 90 mass %.
[0179] [Method for producing the present composition] The present composition can be produced, for example, by mixing the copolymer (a) and the above-mentioned other components used as necessary by a known method using a stirring device or the like.
[0180] When the components are mixed and stirred, the components may be mixed and stirred all at once or sequentially.
[0181] The stirring conditions are not particularly limited, but from the viewpoint of workability and productivity, the stirring may be carried out at room temperature for about 10 to 120 minutes.
[0182] [Method for forming the adhesive layer] The adhesive layer can be formed, for example, by applying the composition to the polarizing film or support, and causing the composition to undergo a cross-linking reaction, thereby forming the adhesive layer on the polarizing film or support. Alternatively, after applying the composition to the polarizing film or support, a support or the polarizing film can be arranged on the coated surface as needed to cause the composition to undergo a cross-linking reaction.
[0183] Alternatively, the present adhesive layer may be formed by applying the present composition to an adherend and then placing the polarizing film on the applied surface.
[0184] Thus, as a preferred embodiment of the present adhesive layer obtained by subjecting the present composition to a crosslinking reaction, there can be mentioned an embodiment comprising a crosslinked product obtained by subjecting the copolymer (a) to an isocyanate-based crosslinking agent, and further an embodiment comprising complexing the remaining isocyanate-based crosslinking agent self-condensate which does not contribute to the crosslinking reaction with at least one selected from the copolymer (a) and a crosslinked product of the copolymer (a).
[0185] The support may be a release-treated substrate.
[0186] The substrate is not particularly limited, and may, for example, be a resin plate, a glass plate, a woven fabric, a nonwoven fabric, or paper.
[0187] The resin is preferably a transparent resin, and examples of the transparent resin include polycarbonate (PC), polymethyl methacrylate (PMMA), polyethylene terephthalate (PET), polypropylene (PP), acrylonitrile-butadiene-styrene copolymer (ABS), and polyamide (nylon).
[0188] The composition may be applied by a known method such as spin coating, knife coating, roll coating, bar coating, doctor blade coating, die coating or gravure coating until the resulting adhesive layer reaches a predetermined thickness.
[0189] In addition, depending on the situation, the polarizing film or the support may be immersed in the present composition instead of coating, and the present composition may be disposed on the polarizing film or the support.
[0190] After the present composition is applied to a polarizing film or a support, the applied present composition may be dried as required. The drying conditions vary depending on the type of solvent, but examples thereof include drying at 50 to 150° C., preferably 60 to 100° C., for usually 1 to 10 minutes, preferably 2 to 7 minutes.
[0191] After the present composition is dried as required as described above, it is preferred to provide a step of curing the present composition. Examples of such curing conditions include curing for usually 3 days or more, preferably 7 to 10 days, at a temperature of usually 5 to 60° C., preferably 15 to 40° C., and usually 5 to 70% RH, preferably 5 to 50% RH. Curing under such conditions allows sufficient crosslinking to occur, and tends to facilitate the formation of an adhesive layer with stabilized physical properties.
[0192] <Method for producing the polarizing film with adhesive layer> The method for producing the polarizing film with an adhesive layer is not particularly limited, but the following method may be mentioned, for example.
[0193] A method for manufacturing a laminate [release-treated substrate / adhesive layer / polarizing film] by the same method as the method described in the above-mentioned method for forming the adhesive layer, or a method for forming a laminate [release-treated substrate / adhesive layer / release-treated substrate] by the same method as the method described in the above-mentioned method for forming the adhesive layer, and peeling off the release-treated substrate on one side of the laminate and attaching a polarizing film to the exposed adhesive layer.
[0194] These laminates having a release-treated substrate can be stored or moved together with the release-treated substrate during storage or transportation, and can be used as the polarizing film with an adhesive layer by peeling off the release-treated substrate when used.
[0195] 《Image display device》 The present polarizing film with an adhesive layer is suitably used in an image display device, and is usually attached to an image display element of the image display device.
[0196] Examples of the image display device include a liquid crystal display and an organic EL display, and examples of the image display element include a liquid crystal element and an organic EL display element.
[0197] As a member to which the present pressure-sensitive adhesive layer-attached polarizing film is bonded, for example, a glass or resin substrate constituting the above-mentioned image display element may be mentioned.
[0198] The image display device using the polarizing film with an adhesive layer is not prone to poor adhesion between the polarizing film with an adhesive layer and the image display element even in a high temperature environment, so the degradation of display performance caused by this can be suppressed. Therefore, the polarizing film with an adhesive layer can be suitably used in image display devices such as those for vehicles that are exposed to high temperatures.
[0199] Furthermore, by using the present polarizing film with an adhesive layer, stress concentrated on the edge portion, in particular, of the polarizing film can be dispersed, and thus the polarizing film can be suitably used in a thin image display device with a narrow frame. Example
[0200] Hereinafter, although embodiment of the present invention is described more specifically based on Examples, the present invention is not limited to these Examples.
[0201] <Weight average molecular weight (Mw), molecular weight distribution (Mw / Mn)> The weight average molecular weight (Mw) and number average molecular weight (Mn) of each polymer were analyzed by gel permeation chromatography (GPC) under the following conditions and calculated in terms of polystyrene. The molecular weight distribution (Mw / Mn) was calculated from the calculated Mw and Mn.
[0202] ·Device: GPC-8220 (manufactured by Tosoh Corporation) Chromatographic column: TSKgel G7000H XL / 7.8mmID×1+TSKgel GMH XL / 7.8mmID×2pcs+TSKgelG2500H XL / 7.8mmID×1 piece (all made by Tosoh Corporation) Medium: Tetrahydrofuran Flow rate: 1.0mL / min Concentration: 1.5 mg / mL Injection volume: 300μL Column temperature: 40℃ [Synthesis example 1] In a reaction apparatus equipped with a stirrer, a reflux cooler, a thermometer, and a nitrogen inlet pipe, 59.9 parts by mass of n-butyl acrylate (BA), 20 parts by mass of methyl acrylate (MA), 18 parts by mass of benzyl acrylate (BzA), 1.9 parts by mass of 2-hydroxyethyl acrylate (2-HEA), 0.2 parts by mass of acrylic acid (AA), and 100 parts by mass of ethyl acetate were added, and the temperature was raised to 70°C while introducing nitrogen. Next, 0.05 parts by mass of 2,2'-azobisisobutyronitrile (hereinafter also referred to as "AIBN") was added, and a first-stage polymerization reaction was carried out at 72 to 73°C for 3 hours under a nitrogen atmosphere, and then 0.02 parts by mass of AIBN was added to carry out a second-stage polymerization reaction for 2 hours, thereby synthesizing polymer A. After the reaction was completed, the reaction solution was diluted with ethyl acetate so that the polymer concentration was 15% by mass, thereby preparing a polymer solution of polymer A. The Mw of the obtained polymer A was 1.6 million, and the Mw / Mn was 8.0.
[0203] [Synthesis example 2] Polymer B was synthesized in the same manner as in Synthesis Example 1 except that the first stage polymerization reaction time was changed to 4 hours and the second stage polymerization reaction was not performed to prepare a polymer solution of polymer B. Mw and Mw / Mn of the obtained polymer B are shown in Table 1.
[0204] [Synthesis example 3] Polymer C was synthesized in the same manner as in Synthesis Example 2 except that the types and amounts of monomers used in Synthesis Example 2 were changed to those shown in Table 1, thereby preparing a polymer solution of Polymer C. Mw and Mw / Mn of the obtained Polymer C are shown in Table 1.
[0205] [Synthesis Example 4] Polymer D was synthesized in the same manner as in Synthesis Example 2 except that the amount of AIBN used was changed to 0.03 parts by mass, thereby preparing a polymer solution of Polymer D. Table 1 shows Mw and Mw / Mn of the obtained Polymer D.
[0206] [Synthesis Example 5] Except that the types of monomers used in Synthesis Example 1 and the amounts thereof used were changed to those shown in Table 1 and the amount of AIBN used in the first stage polymerization reaction was changed to 0.04 parts by mass, polymer E was synthesized in the same manner as in Synthesis Example 1 to prepare a polymer solution of polymer E. Mw and Mw / Mn of the obtained polymer E are shown in Table 1.
[0207] Table 1 The meanings of the monomer symbols in Table 1 are as follows.
[0208] BA: n-butyl acrylate (homopolymer Tg: -50°C) MA: Methyl acrylate (Tg of homopolymer: 8°C) ·BzA: Benzyl acrylate ·2-HEA: 2-Hydroxyethyl acrylate AA: Acrylic acid [Example 1] An isocyanate crosslinking agent TD-75 (manufactured by Soken Chemical Co., Ltd.) and a silane coupling agent A-50 (manufactured by Soken Chemical Co., Ltd.) were added to the polymer solution of polymer A obtained in Synthesis Example 1 and mixed to obtain an adhesive composition. The amount of TD-75 blended was such that the solid content of TD-75 was 0.6 parts by mass relative to 100 parts by mass of the solid content of polymer A, and the amount of A-50 blended was such that the solid content of A-50 was 0.2 parts by mass relative to 100 parts by mass of the solid content of polymer A.
[0209] After removing bubbles from the obtained adhesive composition, the defoamed adhesive composition was applied to a polyethylene terephthalate film (PET film) that had been subjected to a peeling treatment with a doctor blade, and dried at 90° C. for 3 minutes to obtain a sheet having a coating film with a dry film thickness of 20 μm. The coating film surface of the sheet was bonded to the surface of the second protective layer of a polarizing film (first protective layer: triacetyl cellulose (thickness 46 μm) / polarizer: polyvinyl alcohol (thickness 28 μm) / second protective layer: triacetyl cellulose (thickness 20 μm)) to be in contact with each other, and left to mature at 23° C. / 50% RH for 7 days to obtain a polarizing film with an adhesive layer having a PET film.
[0210] [Examples 2 to 6, Comparative Examples 1 to 9] An adhesive composition and an adhesive layer-attached polarizing film were obtained in the same manner as in Example 1 except that the blending composition in Example 1 and the thicknesses of the protective layer and polarizer of the polarizing film used were changed as shown in Table 2.
[0211] In addition, the numerical values in the columns of the crosslinking agent and the silane coupling agent in Table 2 represent the addition amount (parts by mass) of the solid content of each of these components relative to 100 parts by mass of the solid content of the polymers A to E.
[0212] <Gel fraction> After removing bubbles from the obtained adhesive composition, the defoamed adhesive composition was applied to a release-treated PET film with a doctor blade and dried at 90° C. for 3 minutes to form a coating film with a dry film thickness of 20 μm. A release-treated PET film was further attached to the surface of the coating film opposite to the PET film-attached surface, and the coating film was left to stand for 7 days in a 23° C. / 50% RH environment for aging to prepare an adhesive layer with a thickness of 20 μm sandwiched between two PET films.
[0213] About 0.1 g of the prepared adhesive layer was collected in a sampling bottle, 30 mL of ethyl acetate was added, and after shaking for 4 hours, the contents of the sampling bottle were filtered through a 200-mesh stainless steel wire mesh, and the residue on the wire mesh was dried at 100°C for 2 hours and the dry mass was measured. The gel fraction of the adhesive layer was calculated by the following formula.
[0214] Gel fraction (%) = (dry mass / adhesive layer collection mass) × 100 (%) <Adhesion> The polarizing film with an adhesive layer having a PET film obtained in the examples and comparative examples was cut into a strip with a width of 25 mm to prepare a test piece. The PET film was peeled off from the prepared test piece, and the exposed adhesive layer was pasted on a glass plate and pressed with a 2 kg roller. The glass plate to which the obtained polarizing film with an adhesive layer was pasted was autoclaved at 50°C and 5atm for 20 minutes, and then allowed to stand for 1 hour in an environment of 23°C / 50%RH. Thereafter, one end of the polarizing film was stretched at a stretching rate of 300mm / min in a direction of 180° relative to the pasting surface, and the adhesive force (peel strength) required for peeling was measured.
[0215] <High temperature durability (115℃×750hr)> The polarizing film with adhesive layer having PET film obtained in the examples and comparative examples was cut into 150 mm × 250 mm, the PET film was peeled off, and it was pasted on a glass plate with a thickness of 1.1 mm, and pressed with a 2 kg roller. The glass plate to which the polarizing film with adhesive layer was pasted was autoclaved at 50°C and 5 atm for 20 minutes, and then placed at 23°C / 50% RH for 24 hours to prepare a sample for high temperature durability evaluation.
[0216] The prepared high-temperature durability evaluation sample was left to stand for 750 hours in an environment of 115° C. Then, it was taken out and left to stand for 24 hours in an environment of 23° C. / 50% RH, and the adhesiveness and anti-foaming property of the adhesive layer were visually evaluated according to the following criteria.
[0217] (Adhesion) ○: No poor adhesion was observed.
[0218] ○△: Although crack-like adhesion failure slightly occurred in the adhesive layer, no practical problem occurred.
[0219] Δ×: Adhesion failure in the form of cracks occurred in the adhesive layer, and there is a possibility of causing practical problems.
[0220] ×: Peeling occurred between the adhesive layer and the polarizing film or the glass plate.
[0221] (Foaming resistance) ○: No foaming was observed.
[0222] △: Fine foaming slightly occurs, but does not cause any practical problem.
[0223] ×: Foaming occurs significantly, and there is a possibility of causing practical problems.
[0224] -: Evaluation of the occurrence of peeling was omitted.
[0225] <Contraction distance> Samples for shrinkage distance measurement were prepared in the same manner as in the preparation of the samples for high-temperature durability evaluation, except that the polarizing films with adhesive layers having PET films obtained in Examples and Comparative Examples were cut into 115 mm×230 mm.
[0226] The sample for measuring the shrinkage distance prepared in the above manner was left to stand for 250 hours in an environment of 115°C. Then, it was taken out and left to stand for 24 hours in an environment of 23°C / 50% RH, and the shrinkage distance of the polarizing film was measured under a microscope. The shrinkage distance is the average value of the shrinkage distance (mm) in the long side direction at three points at the ends and the center of the short side of the sample for measuring the shrinkage distance (the length in the long side direction before standing at 115°C for 250 hours (mm) - the length in the long side direction (mm) after standing at 115°C for 250 hours).
[0227] When the shrinkage distance is 800 μm or less, shrinkage of the polarizing film can be suppressed, which is good. If the shrinkage distance exceeds 800 μm, for example, practical problems may occur in image display devices with narrow frames.
[0228] Table 2 The meanings of the symbols for the crosslinking agent, silane coupling agent and protective layer material in Table 2 are as follows.
[0229] TD-75: Trimethylolpropane adduct of xylene diisocyanate (manufactured by Soken Chemical Co., Ltd.) ·A-50: Silane coupling agent (manufactured by Soken Chemical Co., Ltd.) ·TAC: Triacetyl Cellulose As shown in Table 2, the polarizing film with an adhesive layer in each example had appropriate adhesive strength, excellent durability in a high temperature environment, and the shrinkage of the polarizing film was suppressed, thereby obtaining good results.
[0230] On the other hand, in Comparative Examples 1, 2, 4, 7, and 8 where the thickness ratio of the first protective layer to the second protective layer was not within the range of 0.1 to 0.7, the high-temperature durability of the polarizing film with an adhesive layer and the suppression of shrinkage of the polarizing film were insufficient.
[0231] Furthermore, the polarizing films with adhesive layers in Comparative Examples 6 to 9 using (meth)acrylic copolymers not containing 10 to 50% by mass of a (meth)acrylic acid alkyl ester having a homopolymer Tg of 0° C. or higher had insufficient high temperature durability and reduced shrinkage of the polarizing films.
[0232] Furthermore, in Comparative Examples 3, 5, and 9 in which the gel fraction of the adhesive layer was 80% or less, the high-temperature durability of the polarizing film with an adhesive layer and the shrinkage suppression of the polarizing film were also insufficient.
Claims
1. A polarizing film with an adhesive layer, comprising: a polarizing film having a first protective layer on one side of a polarizer and a second protective layer on the other side of the polarizer, and an adhesive layer in contact with the second protective layer, The ratio of the thickness of the first protective layer to the thickness of the second protective layer, that is, the thickness of the second protective layer / the thickness of the first protective layer, is 0.1 to 0.
7. The adhesive layer is a layer formed of an adhesive composition containing a (meth)acrylic polymer. The (meth)acrylic copolymer is a copolymer of a monomer mixture containing 10 to 50% by mass of an alkyl (meth)acrylate having a homopolymer glass transition temperature (Tg) of 0° C. or higher. The adhesive layer has a gel fraction greater than 80%.
2. The polarizing film with an adhesive layer according to claim 1, wherein The (meth)acrylic acid-based copolymer has a weight average molecular weight of 800,000 to 2,000,000.
3. The polarizing film with an adhesive layer according to claim 1, wherein The molecular weight distribution of the (meth)acrylic acid copolymer is 5-12.
4. The polarizing film with an adhesive layer according to claim 1, wherein The polarizing film has a thickness of 10 to 150 μm.
5. The polarizing film with an adhesive layer according to claim 1, wherein The first protective layer and the second protective layer include at least one resin selected from the group consisting of a (meth)acrylic resin, a cellulose resin, a cycloolefin polymer resin, and a polyvinyl alcohol resin.
6. An image display device, wherein: The polarizing film with an adhesive layer according to any one of claims 1 to 5 is bonded to an image display element.
Citation Information
Patent Citations
Polarizing plate and image display device using the same
JP2007058183A